2014
DOI: 10.1186/1743-0003-11-18
|View full text |Cite
|
Sign up to set email alerts
|

Revealing spatio-spectral electroencephalographic dynamics of musical mode and tempo perception by independent component analysis

Abstract: BackgroundMusic conveys emotion by manipulating musical structures, particularly musical mode- and tempo-impact. The neural correlates of musical mode and tempo perception revealed by electroencephalography (EEG) have not been adequately addressed in the literature.MethodThis study used independent component analysis (ICA) to systematically assess spatio-spectral EEG dynamics associated with the changes of musical mode and tempo.ResultsEmpirical results showed that music with major mode augmented delta-band ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 52 publications
5
16
0
Order By: Relevance
“…According to the Talairach coordinates, the five regions were source localized around the anterior cingulate cortex (ACC, Brodmann area 32) in the frontal region, the cingulate gyrus in the central region, the left and right inferior temporal gyrus (ITG, Brodmann area 20 and 35), and the posterior cingulate cortex (PCC, Brodmann area 25) in the parietal region. Similar or close dipole locations have also been reported by previous studies employing auditory tasks (Nolden et al, 2013; Lin et al, 2014; MacLean and Ward, 2014).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…According to the Talairach coordinates, the five regions were source localized around the anterior cingulate cortex (ACC, Brodmann area 32) in the frontal region, the cingulate gyrus in the central region, the left and right inferior temporal gyrus (ITG, Brodmann area 20 and 35), and the posterior cingulate cortex (PCC, Brodmann area 25) in the parietal region. Similar or close dipole locations have also been reported by previous studies employing auditory tasks (Nolden et al, 2013; Lin et al, 2014; MacLean and Ward, 2014).…”
Section: Resultssupporting
confidence: 89%
“…The aim of this study was to explore the neural dynamics contributing to musical working memory with our newly established natural musical DMST. Consistent with previous EEG and MEG findings in auditory working memory (Nolden et al, 2013; Lin et al, 2014; MacLean and Ward, 2014), our ICA and dipole fitting results showed elevated activation in corresponding regions, such as the left and right inferior temporal gyrus, anterior cingulate cortex, and posterior cingulate cortex, which have been reported to be correlated with the retention of auditory short-term memory, the perception of retention, and memory load, respectively (Nolden et al, 2013). We also demonstrated the following findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In these studies, brain signals were recorded using an EEG headset while the subject listens to music [44,53,58,100,110,112,115,116,151,154,190,205,216,220,222,235,276,279]. Moreover, the subjects' emotions were recognized as displayed by EEG signals.…”
Section: Domain Description Referencesmentioning
confidence: 99%
“…Music perception is a complex cognitive task that involves the integration of the various structural components of music (melody, harmony, rhythm, tempo, and others). Different neural correlates have been associated with the music perception ( Platel et al, 1997 ; Schmithorst et al, 2005 ; Gomez and Danuser, 2007 ; Lin et al, 2014 ). Hadjidimitriou et al (2010) studied the EEG signals including the Mu rhythm in groups of advanced music students and non-musicians on the movements during the sound and audiovisual stimulation.…”
Section: Non-drug Ways To Reactivate the Plasticity Of The Adult Braimentioning
confidence: 99%